(untitled) (The International Research Journal of Management Science, 2021)
When it comes to determining a dividend policy that would maximize shareholder value, focusing merely on how much of the firm’s profit is necessary for dividend distribution and reinvestment is insufficient. It is critical to analyze the impact of their dividend choice on the stock price.The purpose of this study is to scrutinize the impact of dividend policy on stock price volatility. The report investigated the relationship between the dividend policy and stock price volatility taking 8 articles between 2010 to 2020. Likewise, following a systematic literature review method, the study critically analyzed the selected articles based on their strengths and weaknesses. The findings suggest that, in most of the cases demonstrated by authors, dividend policy has a significant negative relationship with the stock price volatility. The stock’s price volatility often decreases after the declaration of dividend payout ratio and dividend yield. Based on the results of this study, it can be implied that, managers of manufacturing companies and banks, those listed in the stock exchange, may be able to reduce the price volatility of their stock by increasing dividend payout and dividend yield. Since the study is limited to 4 databases, further studies could include some more articles from top-rated databases that signify dividend policy in diverse sectors to derive even more accurate results.